Busworld Website Development To Improve Business Vocabulary Achievement Of Vocational School Marketing Students - Syntia Afriliani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study intends to ascertain the potential, issues, and requirements for learning English for marketing majors at vocational schools. It also seeks to evaluate the feasibility of the Busworld website, which was created as an alternate medium for this research. English communication abilities must be improved by vocational students. Issues that arise with marketing majors at vocational schools show that the same materials are still used in both general education and vocational education. A notable example of technology use in this study is the technology-based learning medium, which took the shape of a website centered around telecommunications. The Sugiyono Model is the model that is adapted for this research, which employs the Research and Development (R&D) technique. Finding Potential, Problems, and Data Analysis, Design Validation, Product Design, Product Testing, Product Revision, Final Product, and Publication are the steps that have been modified. The SMK Pemuda 1 Kesamben, SMK PGRI 2 Sutojayan, and SMKN 1 Kademangan served as the research's field sites. This study's data is quantitative in the form of teacher and student answers and product validation results, and qualitative in the form of observations, interviews, and documentation. The study's findings suggest that using the Busworld website as an alternate medium can help marketing students expand their vocabulary related to business. The results of the media validation and material validation, which were completed by three experts each, and which yielded a score of 98%, indicating high validity, serve as evidence for this. Additionally, 88.5% of the replies from thirty marketing students and three teachers were included in the results of the teacher and student surveys. In summary, the Busworld website, which offers resources such as 100 lists of verbs, 100 lists of nouns, 50 business abbreviations, and 50 conversations with business themes, is a valuable tool for improving the business vocabulary proficiency of marketing students at vocational schools.